1978
DOI: 10.1172/jci108934
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Studies of Erythrocytes from Patients with Duchenne Muscular Dystrophy

Abstract: A B S T R A C T The membrane organization of the erythrocytes from patients with Duchenne muscular dystrophy was studied by means of electron spin resonance. The fluiidity of the membrane near the polar region of Duchenine muscular dystrophy ervthrocytes was similar to that of normal erythrocytes. The membrane environment in the nonpolar region, however, was quite different from that of normal erythrocytes, judged by the spectra with 2-(14-carboxytetradecyl) -2 -ethyl -4,4 -dimethyl -3 -oxazolidinvloxyl as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 30 publications
(29 reference statements)
2
43
0
Order By: Relevance
“…Fluorescence polarization studies of leukemic lymphocytes (18) and ESR studies of erythrocytes from muscular dystrophy patients (19,20) have revealed fluidity abnormalities for these formed elements of the blood. In this study we have used spin label ESR to characterize the membrane fluidity of intact, viable CHS PMN and isolated membrane fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence polarization studies of leukemic lymphocytes (18) and ESR studies of erythrocytes from muscular dystrophy patients (19,20) have revealed fluidity abnormalities for these formed elements of the blood. In this study we have used spin label ESR to characterize the membrane fluidity of intact, viable CHS PMN and isolated membrane fractions.…”
Section: Discussionmentioning
confidence: 99%
“…An increased erythrocyte membrane fluidity was observed in myotonic muscular dystrophy and congenital myotonia (8) . Abnormalities in the lateral diffusion of 5DS (43), in a lipid-protein interaction (37), and in the physical state of membrane proteins (7) have been observed in RBC membranes in Duchenne muscular dystrophy . In Huntington's disease, alterations in the physical state of erythrocyte membrane proteins (9) and in erythrocyte deformability (10) were found.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is not possible to state whether this alteration is a primary abnormality in Ducheme muscular dystrophy or whether it might be secondary to some other disorder. For example, the proposed membrane dysfunction in Duchenne muscular dystrophy (1 I, 25,26,28,29,37,40) could lead to depletion of ATP concentrations in muscle cells. The increased consumption of ATP to maintain cellular homeostasis could accelerate purine nucleotide turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent hypotheses to explain the disorder have included a structural membrane abnormality (I I, 25,26,28,29,37,40) or an accelerated state of protein degradation in dystrophic muscle (16, 3 1). It is at present difficult to discern which of these possibilities may be correct or indeed, whether both types of disorders may result from a more fundamental abnormality in the dystrophic muscle cell.…”
Section: Speculationmentioning
confidence: 99%